Indonesian Children Poetry as The Learning Medium of English Subject in Elementary School - Mulyono, Tri; Nuryatin, Agus; Asayuti, Suminto; Rustono, Mr (Jurnal Bahasa Inggris, 2017)
Learning will be effective when it is conducted with fun. In line with this, by using Indonesian children poetry as the medium of learning, English learning can be done in a fun way. Moreover, Indonesian children poetry is a poetry written intentionally for children, that is those whose ages range from 2 up to 12 years old. With this underlying idea, this paper was written with the aim of describing English learning with the medium of Indonesian children poetry. The result shows that English learning is possible to be done by using Indonesian children poetry as the medium.